Comparative analysis of dose calculation algorithms for CyberKnife-based stereotactic radiotherapy in lung cancer - Ge, Xuanchu; Yang, Mingshan; Li, Tengxiang; Liu, Tonghai; Gao, Xiangyu; Qiu, Qingtao; Yin, Yong (Frontiers in Oncology, 2023)
This study compared three different CK dose algorithms based on CLC and UCLC cases. The results showed that most dose parameters of PTV and OARs demonstrated the trend of MC > FSPB_LS > FSPB. The FSPB_LS algorithm significantly improved the calculation accuracy of the traditional FSPB algorithm and exhibited dose distributions similar to MC within the PTV. However, for CLC, there were significant differences between the FSPB_LS algorithm and the MC algorithm in terms of OARs. Although these differences reduced in UCLC, the OARs in UCLC were highly sensitive to dose variations. In conclusion, we recommend using the MC algorithm for dose calculation in CLC and UCLC. The findings of this study provide important guidance for algorithm selection in MLC-based CK planning, helping radiation oncologists gain intuitive insights into the differences among various dose algorithms in CLC and UCLC, and offering beneficial references for clinical algorithm choices.